Marketing Singapore : heritage sites for sustained tourism growth. - Teo, Yoke Theng. (2013)
The aim of this study is to establish if heritage tourism can be a vehicle for sustained tourism growth in Singapore, and explore tourists’ preferred mix of activities within a heritage zone. 107 tourists were surveyed in Singapore and subsequently distinguished between heritage and non-heritage tourists.